أثر الضرائب البيئية في الحد من التلوث البيئي: ايطاليا انموذجاً للمدة 1995-2017 - فارس جار الله نايف; علاء وجيه مهدي النعمه (PROSPECTIVE RESEARCHES, 2023)
Environmental taxes contribute significantly to reducing the environmental problem, as well as reducing the carbon emissions of carbon dioxide (CO2). And the results of the standard analysis in Italy for the peroide (1995-2017), indicated that there is an inverse relationship between environmental takes and carbon dioxide emessions, which means that increasing environmental taxes by 1% leads to a decrease in the emission of carbon dioxide by (673.04) units. There is a positive correlation between foreign direct investment and the emission of carbon dioxide, possibly as a result of the multiple use of economic resources andnon-renewable energy, a negative impact. The other indicators are of varying effect because the population growth is not significant during the period under study, which may be due to the low population growth rates significantly environmental pollutants. The research looks at its theoretical side to what environmental pollution is, as well as what environmental taxes are.